2020
DOI: 10.1002/jsfa.10967
|View full text |Cite
|
Sign up to set email alerts
|

Reflective mulch increases fruit yield of highbush blueberry (Vaccinium corymbosum L. cv. Darrow) grown in a northern maritime environment while maintaining key fruit quality traits

Abstract: BACKGROUND: In maritime growing environments, blueberry yield often exhibits excessive season-to-season variation, associated with poorly adapted photosynthetic responses to low light conditions. It is therefore necessary to develop methods that stabilise yield while maintaining or improving fruit quality. Here, we placed reflective mulch alongside plants at the early green fruit stage, to test the hypothesis that increasing the available seasonal light integral could enhance blueberry yield. We further determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
2
4
0
Order By: Relevance
“…Todic et al (2008) showed that application of reflective plastic foils increased total phenolic and anthocyanin content of Cabernet Sauvignon (Vitis vinifera L.) grapes (Todic et al, 2008). Furthermore, in maritime growing environments subjected to low light conditions, placement of reflective mulches alongside blueberry plants enhanced the total anthocyanin content and antioxidant activity of fruits (Petridis et al, 2021). Similar results were reported by Magee and Spiers (1996) who showed that mulching preserved the sugar and anthocyanin content of blueberries (Magee & Spiers, 1996).…”
Section: Mulchingsupporting
confidence: 79%
“…Todic et al (2008) showed that application of reflective plastic foils increased total phenolic and anthocyanin content of Cabernet Sauvignon (Vitis vinifera L.) grapes (Todic et al, 2008). Furthermore, in maritime growing environments subjected to low light conditions, placement of reflective mulches alongside blueberry plants enhanced the total anthocyanin content and antioxidant activity of fruits (Petridis et al, 2021). Similar results were reported by Magee and Spiers (1996) who showed that mulching preserved the sugar and anthocyanin content of blueberries (Magee & Spiers, 1996).…”
Section: Mulchingsupporting
confidence: 79%
“…Juice samples were analysed for individual anthocyanins as previously described (Petridis et al, 2020). Briefly juice samples were injected onto a Phenomenex Luna C18(2) 5 μm (150 mm × 4.6 mm) column and separated in a non‐linear dual eluent gradient comprising 5% aqueous formic acid and acetonitrile:methanol:formic acid (85:10:5, v/v/v) at a flow rate of 1 ml min −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Anthocyanin identification was achieved following manual collection of liquid specimens represented by individual peaks which were dried in a centrifugal evaporator. Following resuspension in 20% methanol containing 0.1% formic acid, samples were directly infused into a LCQ-Fleet™ ion trap mass spectrometer to determine the mass of parent and daughter ions under the conditions previously described (Petridis et al, 2020). Compounds were identified according to their HPLC retention times and parent and daughter mass spectra as described in Table 1.…”
Section: Anthocyanin Profiling By Hplc-dadmentioning
confidence: 99%
“…The content of vitamin C (mg/100g FW) in fruits was determined according to the method described by Chanwitheesuk et al [27]. With reference to the description of Petridis et al, the total anthocyanin content in fruits was determined by the pH differential method, and the total phenol content was determined by the Folin-Ciocalteu assay [14]. Total flavonoid content was calculated as rutin equivalents and determined according to the method of Wang et al [28].…”
Section: Fruit Quality Parameters Measurementsmentioning
confidence: 99%
“…Highbush blueberry (Vaccinium corymbosum L.) is an important perennial deciduous fruit shrub that belongs to the Ericaceae family [14]. Blueberry has become a popular and highly priced small fruit crop because of its high nutraceutical and potential pharmaceutical values [15].…”
Section: Introductionmentioning
confidence: 99%